MUSIKALISASI PUISI SEBAGAI KRITIK SOSIAL: ANALISIS LAGU “ORA CUCUL ORA NGEBUL” KARYA JOGJA HIPHOP FOUNDATION DARI PUISI SINDHUNATA - Linda Binti Lestari; Zizin Nur Sa’idah; Fauzil Adhim; Handy Agustiar Imansyah; Moh. Fikri Zulfikar (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2025)
This study analyzes the musicalization of poetry as a medium for social criticism, focusing on the song "Ora Cucul Ora Ngebul" by Jogja Hiphop Foundation, adapted from a poem by Sindhunata. Using a qualitative descriptive approach with content analysis, this research examines how poetic messages of poverty, hard work, and structural inequality are transformed into a contemporary musical form. Data collection was conducted through documentation and literature review, then analyzed thematically and intertextually. The findings show that Jogja Hiphop Foundation successfully reinterprets Sindhunata’s social criticism by integrating local language, traditional elements, and the global genre of hip-hop. Through music, the emotional depth and urgency of social critique are amplified, making it accessible and resonant with a younger, broader audience. The musicalization process does not merely preserve the core meaning of the poem but revitalizes its relevance by addressing ongoing issues in Indonesian society, such as economic disparity and injustice. This study concludes that musicalized poetry can serve as a powerful cultural strategy to express collective social concerns, build awareness, and inspire transformative reflection through contemporary media.